2022
DOI: 10.1108/et-03-2021-0106
|View full text |Cite
|
Sign up to set email alerts
|

Business students' perspectives on case method coaching for problem-based learning: impacts on student engagement and learning performance in higher education

Abstract: Purpose The aim of this study is to examine the experiences of business students on case method coaching for problem-based learning and its influence on student engagement and learning performance in the context of Malaysian private higher education.Design/methodology/approach This study applied quantitative method with a self-administered questionnaire survey was used to collect data from 410 undergraduate business students from five top private universities in Malaysia using convenience sampling. Structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Al-Madi et al (2018) and Liu et al (2019) have seen the positive impact of PBL on knowledge for dental students using paired t-test. Also, Song et al (2022) have observed a positive correlation between student engagement and learning performance with PBL.…”
Section: Discussionmentioning
confidence: 86%
“…Al-Madi et al (2018) and Liu et al (2019) have seen the positive impact of PBL on knowledge for dental students using paired t-test. Also, Song et al (2022) have observed a positive correlation between student engagement and learning performance with PBL.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, Tomaszewski et al (2020) argued that student engagement mediates the relationship between students’ socioeconomic status (SES) and academic achievement. Other studies have demonstrated that teaching methods and learning environment are factors related to academic performance, and the relationships between these variables and academic performance are mediated by student engagement ( Simpson and Burnett, 2019 ; Song et al, 2022 ). This study found that classroom climate perceived by English-major teacher education students improved their academic performance by promoting their student engagement, suggesting that student engagement was an important factor associated with academic performance, which supported the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relationship between teaching methods, learning environment, socioeconomic status and academic performance are all mediated by student engagement. For example, the case method of instruction improves students’ academic performance by enhancing their engagement ( Song et al, 2022 ). A study on day or boarding students’ academic performance shows that whether students live in school or not, the critical factor related to their academic performance is student engagement ( Simpson and Burnett, 2019 ).…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the case method and research projects in problem-based learning [34,35] as well as the use of distance learning technology in online, mixed and flipped format has been analyzed [36,37].…”
Section: Literary Reviewmentioning
confidence: 99%